Impact of Financial Inclusion on Rural Development in Rajasthan (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Financial inclusion is a key driver for economic growth, particularly in rural areas where access to financial services is limited. This paper evaluates the impact of financial inclusion on rural development in Rajasthan, analyzing how banking penetration, credit accessibility, and digital financial services contribute to socio-economic upliftment. A survey of rural households and secondary data from financial institutions provide insights into the effectiveness of financial inclusion initiatives.